2016
DOI: 10.1056/nejmoa1602014
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon or Radiofrequency Ablation for Paroxysmal Atrial Fibrillation

Abstract: In this randomized trial, cryoballoon ablation was noninferior to radiofrequency ablation with respect to efficacy for the treatment of patients with drug-refractory paroxysmal atrial fibrillation, and there was no significant difference between the two methods with regard to overall safety. (Funded by Medtronic; FIRE AND ICE ClinicalTrials.gov number, NCT01490814.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
1,438
10
43

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,620 publications
(1,572 citation statements)
references
References 20 publications
81
1,438
10
43
Order By: Relevance
“…Całkowita PVI na poziomie przedsionków jest najlepiej udokumentowanym celem ablacji przezcewnikowej [716,[729][730][731], możliwym do uzyskania przez ablację prądem o wysokiej częstotliwości (RF) prowadzoną punkt po punkcie, wykonywanie liniowych uszkodzeń dookoła żył płucnych lub ablację za pomocą kriobalonu; wszystkie z podobnymi wynikami leczenia [732][733][734]. Całkowita PVI wiąże się z lepszymi wynikami leczenia pod względem utrzymywania rytmu zatokowego niż niecałkowita izolacja [716].…”
Section: Metody I Technologieunclassified
See 1 more Smart Citation
“…Całkowita PVI na poziomie przedsionków jest najlepiej udokumentowanym celem ablacji przezcewnikowej [716,[729][730][731], możliwym do uzyskania przez ablację prądem o wysokiej częstotliwości (RF) prowadzoną punkt po punkcie, wykonywanie liniowych uszkodzeń dookoła żył płucnych lub ablację za pomocą kriobalonu; wszystkie z podobnymi wynikami leczenia [732][733][734]. Całkowita PVI wiąże się z lepszymi wynikami leczenia pod względem utrzymywania rytmu zatokowego niż niecałkowita izolacja [716].…”
Section: Metody I Technologieunclassified
“…Częstoskurcz spowodowany makroobwodem re-entry w obrębie lewego przedsionka jest stosunkowo rzadki po PVI (ok. 5%). Wydaje się, że jest on rzadki również po ablacji za pomocą kriobalonu [734], natomiast może występować nawet u 25% pacjentów po ablacji modyfikującej substrat arytmii w obrębie lewego przedsionka, często z powodu niepełnych linii ablacji. Dlatego u pacjentów z przetrwałym AF ablacja złożonych frakcjonowanych elektrogramów, ablacja rotorów, rutynowe wykonywanie liniowych uszkodzeń lub inne dodatkowe ablacje nie wydają się uzasadnione podczas pierwszego zabiegu [735,738,739].…”
Section: Metody I Technologieunclassified
“…[5] Total procedure time in the latter study is likely highest due to four cavotricuspid isthmus ablations, and one ablation of roof dependent LA tachycardia which was performed during the course of PVI. Summarized, total procedure times reported from the nMARQ TM device compared well with procedure times obtained from other PVI ablation modalities (Cryoballoon: 136 to 371 min [20], [30], [31] ; PVAC: 121 to 137.1 min [32], [33] ; RF 140.9 to 165 min [19], [25] [18] Mean fluoroscopy times varied over a broad range, from 1.8 minutes [7] to 35.5 minutes. [5] In the latter study, the prolonged fluoroscopy times may be explained by additional CMC use in order to confirm complete PVI.…”
Section: Procedural Resultsmentioning
confidence: 82%
“…[18] For those patients that underwent ablation of paroxysmal AF, recurrence rates were between 22.8% and 35% [3], [16] , and are comparable to those obtained by conventional RF, Cryoballoon, or different circumferential RF ablation catheters (PVAC) after one year (between 30.1 -35.9%). [19]- [21] The very low recurrence rate of 22.8% reported by Rodriguez et al may be in parts attributable to the fact that all patients were administered AAD during the blanking period. [16] Burri et al reported recurrence rates of 54% over 15 + 4 months which were considerably higher than other published studies .…”
Section: Acute Efficacy Of Nmarq Tm Guided Ablationmentioning
confidence: 99%
“…Recent randomized clinical studies1 and meta‐analyses2 showed comparable outcomes for CB‐PVI and standard radiofrequency PVI; however, both procedures are associated with the risk of complications. Right phrenic nerve palsy occurs almost exclusively following CB‐PVI 3.…”
Section: Introductionmentioning
confidence: 99%